WORD PROBLEM-SOLVING: THE CASE OF A STUDENT WITH DYSLEXIA - Pelczer, Ildiko; Polotskaia, Elena; Fellus, Olga (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2021)
In our previous studies, we developed an approach to teaching problem-solving we termed Equilibrated Development that allows students to better understand the quantitative relationships that arise in a mathematical problem and to better choose a solution strategy. We used the method of a teaching experiment to evaluate the applicability of the developed approach to cases of students with dyslexia and to modify it, if necessary, to meet these students’ needs. Our data suggest that: a) the understanding of the mathematical structure of a problem is independent of the student’s basic numerical knowledge, and b) there are conditions that allow a dyslexic student to develop mathematical reasoning to solve written problems despite difficulties in reading and writing of numbers and text.